(untitled) (Bioscience Journal, 2022)
This study was designed to compare the effects of Jinkui Shenqi and Wuzi Yanzong pill on sperm motility and sperm DNA fragmentation rate in patients with asthenospermia. 130 cases were randomly divided into an observation and control group (n=65). The control group was treated with the Wuzi Yanzong pill while the observation group with the Jinkui Shenqi pill. The sperm motility parameters rate (PR), semen concentration, sperm motility, DFI and α-glucosidase, fructose, seminal plasma zinc (Zn), acid phosphatase (ACP) in seminal plasma biochemistry and other indexes of were observed. The biochemical indexes of seminal plasma of α-glucosidase, fructose, Zn, ACP in two groups were significantly (p<0.05) improved after treatment. Compared with the control group, the indexes of the observation group improved more obviously after treatment. Pearson correlation analysis of DFI and PR indexes in 130 patients before treatment showed that sperm DFI and PR percentage were negatively correlated in asthenospermia patients (r =-0.572, P<0.05). There was no significant difference in DFI, semen concentration, PR, and sperm motility between the two groups before treatment. The DFI, semen concentration, PR and sperm viability of the two groups showed a tendency to improve after treatment, and the effect of the observation group was less significant than that of the control group (p<0.05). Two groups of patients have completed treatment successfully, no adverse events occurred during treatment. Jinkui Shenqi pill can effectively treat asthenospermia, which can effectively improve the effect of sperm motility in patients. It has less adverse reactions, safe and reliable, and is worthy of promotion.